Berberine Reduces cAMP-Induced Chloride Secretion in T84 Human Colonic Carcinoma Cells through Inhibition of Basolateral KCNQ1 Channels - Alzamora, Rodrigo; O'Mahony, Fiona; Ko, Wing-Hung; Yip, Tiffany W.; Carter, Derek; Irnaten, Mustapha; Harvey, Brian J. (Frontiers in Physiology, 2011)
Berberine is a plant alkaloid with multiple pharmacological actions, including antidiarrhoeal activity and has been shown to inhibit Cl- secretion in distal colon. The aims of this study were to determine the molecular signalling mechanisms of action of berberine on Cl- secretion and the ion transporter targets. Monolayers of T84 human colonic carcinoma cells grown in permeable supports were placed in Ussing chambers and short-circuit current measured in response to secretagogues and berberine. Whole-cell current recordings were performed in T84 cells using the patch-clamp technique. Berberine decreased forskolin-induced short-circuit current in a concentration-dependent manner (IC50 80  8 M). In apically permeabilized monolayers and whole-cell current recordings, berberine inhibited a cAMP-dependent and chromanol 293B-sensitive basolateral membrane K+ current by 88%, suggesting inhibition of KCNQ1 K+ channels. Berberine did not affect either apical Cl- conductance or basolateral Na+-K+-ATPase activity. Berberine stimulated p38 MAPK, PKC and PKA, but had no effect on p42/p44 MAPK and PKC. However, berberine pre-treatment prevented stimulation of p42/p44 MAPK by epidermal growth factor. The inhibitory effect of berberine on Cl- secretion was partially blocked by HBDDE (65 %), an inhibitor of PKC and to a smaller extent by inhibition of p38 MAPK with SB202190 (15 %). Berberine treatment induced an increase in association between PKC and PKA with KCNQ1 and produced phosphorylation of the channel. We conclude that berberine exerts its inhibitory effect on colonic Cl- secretion through inhibition of basolateral KCNQ1 channels responsible for K+ recycling via a PKC-dependent pathway.